Multicenter prospective randomized study comparing the technique of using a bovine pericardium biological prosthesis reinforcement in parietal herniorrhaphy (Tutomesh TUTOGEN) with simple parietal herniorrhaphy, in a potentially contaminated setting. Issue 2 (March 2016) - Nedelcu, Marius; Verhaeghe, Pierre; Skalli, Mehdi; Champault, Gerard; Barrat, Christophe; Sebbag, Hugues; Reche, Fabian; Passebois, Laurent; Beyrne, Daniel; Gugenheim, Jean; Berdah, Stephane; Bouayed, Amine; et al.
Abstract: The use of parietal synthetic prosthetic reinforcement material in potentially contaminated settings is not recommended, as there is a risk that the prosthesis may become infected. Thus, simple parietal herniorrhaphy, is the conventional treatment, even though there is a significant risk that the hernia may recur. Using new biomaterials of animal origin presently appears to offer a new therapeutic solution, but their effectiveness has yet to be demonstrated. The purpose of this multicenter prospective randomized single‐blind study was to compare the surgical treatment of inguinal hernia or abdominal incisional hernia by simple parietal herniorrhaphy without prosthetic reinforcement (Group A), with Tutomesh TUTOGEN biological prosthesis reinforcement parietal herniorrhaphy (Group B), in a potentially contaminated setting. We examined early postoperative complications in the first month after the operation, performed an assessment after one year of survival without recurrence and analyzed the quality of life and pain of the patients (using SF‐12 health status questionnaire and Visual Analog Pain Scale) at 1, 6, and 12 months, together with an economic impact study. Hundred and thirty four patients were enrolled between January 2009 and October 2010 in 20 French hospitals. The groups were comparable with respect to their enrollment characteristics, their history, types of operative indications and procedures carried out. At one month post‐op, the rate of infectious complications ( n (A) = 11(18.33%) vs. n (B) = 12(19.05%), p = 0.919) was not significantly different between the two groups. The assessment after one year of survival without recurrence revealed that survival was significantly greater in Group B (Group A recurrence: 10, Group B: 3; p = 0.0475). No difference in the patients' quality of life was demonstrated at 1, 6, or 12 months. However, at the 1 month follow‐up, the "perceived health" rating seemed better in the group with Tutomesh ( p = 0.022). No significant difference between the two parietal repair groups was observed during the follow‐ups with respect to the criterion of pain (using a visual analog scale). There was a significant difference between the two parietal repair groups with regard to the number of days spent in intensive care unit, in favor of the Tutomesh technique ( p = 0.010). The use of a Tutomesh bioprosthesis for hernia repair or postincisional hernia in a potentially contaminated workplace reduces the risk of short‐term recurrence without increasing overall comorbidity.